Otogenic Lateral Sinus Thrombosis: A Review of Fifteen Patients and Changing Trends in the Management - Raja, Kalaiarasi; Parida, Pradipta Kumar; Alexander, Arun; Surianarayanan, Gopalakrishnan (International Archives of Otorhinolaryngology, 2018)
Introduction Otogenic lateral sinus thrombosis is a rare intracranial complication of otitis media in the modern age of antibiotic treatment, but it is potentially a dangerous complication.Objectives The aim of this study is to focus on the various clinical presentations, management options and sequelae in a series of fifteen patients with otogenic lateral sinus thrombosis.Methods Retrospective chart review of inpatients treated for otogenic lateral sinus thrombosis at our tertiary care institution between 2010 and 2015.Results A total of 15 patients (11 males and 4 females) with ages ranging from 9 to 60 years were diagnosed with otogenic lateral sinus thrombosis. The most commonly reported symptoms were headache, ear discharge and hard of hearing, which were experienced by all 15 (100%) patients. In contrast to previous studies found in the literature, 7 (47%) patients in our series presented with neck pain and neck abscess. Imaging studies and microbiological cultures were performed for all patients, who also underwent a mastoidectomy procedure. Internal jugular vein ligation was performed on 5 (33%) patients. Incision and drainage of the neck abscess was performed on 7 (47%) patients. All patients had a satisfactory resolution of their symptoms, and the mortality rate was of 0%.Conclusions Otogenic lateral sinus thrombosis, though a rare complication, can still occur; therefore, keeping a high level of suspicion is important, especially in developing countries. We also describe the patients with neck abscess associated with this rare condition. Combining parenteral antibiotics with surgical intervention is the treatment of choice.
Keywords: lateral sinus thrombosis; otitis media; cholesteatoma